Convergence in L^p[0,2π]-metric of logarithmic derivative and angular υ-density for zeros of entire function of slowly growth - Mostova, M.R.; Zabolotskyj, M.V. (Carpathian Mathematical Publications, 2015)
The subclass of a zero order entire function f is pointed out for which the existence of angular υ-density for zeros of entire function of zero order is equivalent to convergence in L^p[0,2π]-metric of its logarithmic derivative.